Kontribusi Pendapatan Pedagang Sayur Eceran Terhadap Total Pendapatan Keluarga Di Kelurahan Oesapa Kecamatan Kelapa Lima Kota Kupang - Bella, Florince A; Nampa, I Wayan; Pudjiastuti, Sondang S. P. (Undana Press, 2023)
This research aims to; 1) What is the income of vegetable retailers in Desapa Village, Kelapa Lima District, Kupang City? 2) What is the feasibility of vegetable retailer in Oesapa Village, Kelapa Lima District, Kupang City. 3) How much is the contribution? What is the share of the vegetable retail trade in the family's total income? The determination of the sample in this study was made by an overall sample, where the population was also the sample in the study, since the number of vegetable retailers encountered was not too large, while the data collection was based on a survey method. The data collection took place from May 2022 to June 2022, whereby the collected data was primary data and secondary data and then a data analysis was carried out using qualitative descriptive analysis. The variables measured are costs, revenues, income, relative profits and their contribution to the traders' family income. The results of the study show that (1) the income from running a vegetable retail business is IDR 1,401,015/month. (2) In terms of economic value, the vegetable retailer's business is economically feasible by determining the R/C ratio of 1.5. The R/C ratio of merchants selling in Oesapa village ranges from 1.25 to 1.64(3). The contribution of the vegetable retail business is 53.11%. This shows that the vegetable retail business is a household income source for the vegetable retail business traders.